"Toehold Switches; a foothold for Synthetic Biology". Issue 4 (2nd January 2023) - Yarra, Sai Sumanjali; Ashok, Ganapathy; Mohan, Utpal
Abstract: Toehold switches are de novo designed riboregulators that contain two RNA components interacting through linear‐linear RNA interactions, regulating the gene expression. These are highly versatile, exhibit excellent orthogonality, wide dynamic range, and are highly programmable, so can be used for various applications in synthetic biology. In this review, we summarized and discussed the design characteristics and benefits of toehold switch riboregulators over conventional riboregulators. We also discussed applications and recent advancements of toehold switch riboregulators in various fields like gene editing, DNA nanotechnology, translational repression, and diagnostics (detection of microRNAs and some pathogens). Toehold switches, therefore, furnished advancement in synthetic biology applications in various fields with their prominent features.